The epidemiology of clinical malaria among African children. - Snow, R; Marsh, K (Elsevier, 1998)
There is a resurgence of interest in the clinical epidemiology of malaria among African children. This renewed interest follows fifty years of failure to eradicate infection in Africa and redirected efforts toward disease control and prevention. We have a poor understanding of the mechanisms by which clinical immunity is acquired; however, several recent studies have provided new insights into how fast clinical protection is acquired under the varied transmission intensities common to Africa. What is clear is that the frequency with which individuals encounter infection from birth will determine the speed with which they become clinically immune and the patterns of severe pathology they are likely to experience. There remains doubt and concerns over the long-term consequences of reducing natural parasite exposure in several areas of Africa. New field studies are urgently required to tackle these issues so that control may be guided by an improved understanding of malaria as a disease that can lead to death.